METANARASI SEKS DALAM MAHANIRWANA TANTRA - Suda, Gede; Donder, I Ketut; Widiana, I Gusti Putu Gede (PANGKAJA: JURNAL AGAMA HINDU, 2021)
Sex is a part of life, and even becomes an important part of survival, so that sex is used as a symbol of the cosmos, apart from that, sex is also divided into two, first, the need for procreation, and second, for recreational needs, this is where the problem is when sex it is only used as a recreational need, for the sake of pleasure alone, and to indulge in excessive lust for lack of proper knowledge of sex itself. So, Mahanirwana Tantra is present as a middle way to provide metanarations, that sex is considered to be very extraordinary, more than just sexual intercourse or lust, but a union of energies from two different universal elements, purusha and prakerti. The view of sex in mahanirvana tantra is to be able to provide truth and straighten out general views on the narrative of sex itself, as well as the correct view of the real sexual relationship. Tantra connects sex with God to see the primal origin of humans, those who do not know their origins certainly do not know the way back, the existence of the phallus yoni symbol, or naked holy statues in intercourse is not pornographic, but to invite us to understand our origins. The origin of mankind is still an unfinished debate, all just hypotheses. As a religious person, one should believe that the true origin of life is not from material intercourse, even though the visible process is material.